Mapping phase diagrams of supported lipid bilayers by atomic force microscopy. Issue 1 (22nd March 2016) - Borrell, Jordi H.; Montero, M. Teresa; Domènech, Òscar
ABSTRACT: In this work, we present the method followed to construct a pseudophase diagram of two phospholipids: 1‐palmitoyl‐2‐oleoyl‐ sn ‐glycero‐3‐phosphoethanolamine and 1‐palmitoyl‐2‐oleoyl‐ sn ‐glycero‐3‐phospho‐(1′‐ rac ‐glycerol). Two different techniques, DSC and AFM, have been used based in the determination of the onset ( T onset ) and completion ( T offset ) temperatures of the gel‐to‐liquid crystalline phases ( Lβ →Lα ), the first from the endotherms from liposomes and the second from the topographic images of supported lipid bilayers. The features of both phase diagrams are discussed emphasizing the influence of Ca 2+ presence and the substrate (mica) on the transition undergone by the phospholipid mixture. Microsc. Res. Tech. 80:4–10, 2017 . © 2016 Wiley Periodicals, Inc.